1973
DOI: 10.1098/rspa.1973.0047
|View full text |Cite
|
Sign up to set email alerts
|

Molecular-sieve type sorption on alkali graphite intercalation compounds

Abstract: The sorption of H 2 , D 2 , N 2 , CH 4 and rare gases was studied on alkali graphites C 8 M and C 24 M (M = K, Rb, Cs) at 196-63 K. The C 24 M compounds sorbed gases to various degrees, while all the C 8 M compounds were non-sorptive. The systematic study of the sorption isotherms for all the compound-gas systems revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
23
0

Year Published

1981
1981
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(28 citation statements)
references
References 4 publications
5
23
0
Order By: Relevance
“…In addition, it was reported that when mixed gas of protium (H,) and deuterium (D,) is absorbed in the compounds, the heavier isotope D, is enriched in the absorbed phase (2). It should be noted that the hydrogen absorption in KC, is characterized by the remarkably large isotope effect, as well as the large amount of absorbed gas.…”
Section: (3) (4)mentioning
confidence: 99%
“…In addition, it was reported that when mixed gas of protium (H,) and deuterium (D,) is absorbed in the compounds, the heavier isotope D, is enriched in the absorbed phase (2). It should be noted that the hydrogen absorption in KC, is characterized by the remarkably large isotope effect, as well as the large amount of absorbed gas.…”
Section: (3) (4)mentioning
confidence: 99%
“…The behaviors of these compounds have been known to depend on the structure, sort of metals and temperature. Hydrogens are physisorptively accommodated in the molecules in the interstices among the alkali-metal ions in intercalant layers of stage-2 compounds C 24 M (M = K, Rb and Cs) at temperatures below 200 K [1]- [3]. Chemisorption of hydrogen takes place in both first and second stage compounds at higher temperatures [4] [5].…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Overlapping graphite corrugation potentials from the host GIC structure are another significant feature. Hydrogen adsorption in KC 24 has an isosteric heat 9,10,15 of approximately −9 kJ mol −1 , in comparison to −4 kJ mol −1 for adsorption on graphite. 16 Although the hydrogen molecule is nonpolar, the importance of hydrogen sorption sites with strong Coulomb interactions has been reported for metal-organicframeworks 17 and ion-exchanged zeolites.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] Gas adsorption by KC 24 is known to exhibit molecular-sieving behavior due to size mismatch between the diameters of the sorptive gas molecules and the gap between graphite layers. 9 Extensive inelastic neutron scattering measurements on H 2 /MC 24 (M = K, Rb, Cs) all indicate strong barriers to out-of-plane H 2 rotation, as evidenced by the large splitting of the J = 0 to J = 1 rotational transition. 12 Two kinds of structures for the in-plane alkali metal lattice have been reported: (1) a √ 7 × √ 7 R19.11…”
Section: Introductionmentioning
confidence: 99%